EFEKTIVITAS PENGGUNAAN SISTEM INFORMASI PENGELOLAAN PENGADUAN MASYARAKAT DALAM PEMANFAATAN APLIKASI LAPOR! DI LINGKUNGAN KEMENTERIAN DALAM NEGERI - Akhmad Gibran Akbar; Khasan Effendy; Sampara Lukman (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2021)
This research aimed to reveal how is the use of LAPOR! as an Information System in the Ministry of Home Affairs to manage Public Complaints.Researchers used qualitative methods to describe and gain a thorough and in- depth understanding of the use of the LAPOR! in the management of public complaints within the Ministry of Home Affairs. Based on the concept of the effectiveness of the use of information systems using the DeLone and McLean Model, the researcher can conclude that the LAPOR! have a positive impact and have proven effective in handling public complaints. Because with various technological features that allow accurate and real time communication between the reporter and the manager. The LAPOR! application! It is also considered to provide many benefits to the community, seen from the number of complaints received by the Ministry of Home Affairs from year to year which tends to increase.